2022
DOI: 10.1002/advs.202201420
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide 3′‐UTR Single Nucleotide Polymorphism Association Study Identifies Significant Prostate Cancer Risk‐Associated Functional Loci at 8p21.2 in Chinese Population

Abstract: MicroRNAs (miRNAs) are involved in the regulation of gene expression via incomplete base pairing to sequence motifs at the three prime untranslated regions (3′‐UTRs) of mRNAs and play critical roles in the etiology of cancers. Single nucleotide polymorphisms (SNPs) in the 3′‐UTR miRNA‐binding regions may influence the miRNA affinity. However, this biological mechanism in prostate cancer (PCa) remains unclear. Here, a three‐stage genome‐wide association study of 3′‐UTR SNPs ( n =33 117) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A few years ago, different studies have shown the impact of 3’UTR variants on the expression and susceptibility to cancer development. 18 , 28 , 29 In this study, we were interested in exploring the impact of 3’UTR variants on the gene expression of BRCA1 . In fact, BRCA1, as well as BRCA2, have an important role in the biology of the cell, especially in tumor microenvironment in BC.…”
Section: Discussionmentioning
confidence: 99%
“…A few years ago, different studies have shown the impact of 3’UTR variants on the expression and susceptibility to cancer development. 18 , 28 , 29 In this study, we were interested in exploring the impact of 3’UTR variants on the gene expression of BRCA1 . In fact, BRCA1, as well as BRCA2, have an important role in the biology of the cell, especially in tumor microenvironment in BC.…”
Section: Discussionmentioning
confidence: 99%
“…The conceptual framework and the three MR assumptions of the current study are illustrated in Figure 1; briefly: (i) instrumental variables (single nucleotide polymorphisms [SNP]) are truly associated with the behavioral factors, (ii) SNPs are unrelated to the confounders on the behaviors-PCa nexus, (iii) SNPs affect PCa only via behavioral factors. SNPs were obtained from summary data from reported GWAS and a GWAS cohort of PCa in the East Asian population (Chinese) [13,14]. The study was reported in accordance with the STROBE-MR guidelines [15].…”
Section: Methodsmentioning
confidence: 99%
“…SNPs in the introns can affect RNA splicing and can promote or disrupt the binding and function of long non-coding RNAs (lncRNAs) ( 91 93 ). SNPs located in the 5’- and 3’- untranslated regions (UTRs) may affect protein translation and miRNA-dependent gene silencing ( 94 , 95 ). These aforementioned mechanisms may potentially impact the expression level of MRGPRX2 and lead to the production of variants with different properties.…”
Section: Mrgprx2 Triggering and Its Individual Variability As An Exam...mentioning
confidence: 99%